DESKRIPSI PENGGUNAAN APLIKASI MICROSOFT TEAMS DALAM PEMBELAJARAN DARING MATA PELAJARAN SEJARAH INDONESIA - Ghalyh Wardhana Putra; Hajri Taqin Musthofa; Andriyanto Andriyanto (Keraton: Journal of History Education and Culture, 2020)
The purpose of this study is to describe how the Microsoft Teams application is used in online learning. This study uses a qualitative approach with a descriptive design. The data technique is done by collecting information, interviews, and documentation. The data obtained were then described descriptively. From this method, the research results show that the use of Microsoft Teams in online learning activities is said to be quite effective and efficient. With various features in one application that makes it easier for teachers and students to access, because teachers can deliver materials using various facilities or features provided by the Team, not only in text but also in text. video form. In addition, teachers can also assess the activeness of their students with the chat feature, and can efficiently assign assignments as evaluation materials to see the level of student understanding. In addition, Teams can also be used for video reservations for face-to-face learning via online. This shows that learning using Microsoft Teams is quite efficient in today's online learning process. Keywords: Application, Learning, Microsoft, Online, Teams